Immunomodulatory effect of Rhaphidophora korthalsii on mice splenocyte, thymocyte and bone marrow cell proliferation and cytokine expression - Abd Manaf, Ali (2011)
Rhaphidophora korthalsii methanol extract was previously found as a potential in vitro immunomodulating agent. In this study, the in vitro immunomodulatory activity of R. korthalsii methanol extract on mice splenocyte were quantified through evaluating T/NK cell population. cytokine expression (IL-2 and IFN-y) and cytotoxicity against Yac-1 cell In vitro MTT proliferation study showed that R. korthalsii methanol extract stimulate significant proliferation of splenocyte. thymocyte and bone marrow cell at 25 pg/ml after 72 h incubation as compared to rIL-2. Besides. 25 lig/ma of extract also enhanced T-helper 1 cytokine (IL-2 and IFN-y) secretion. natural killer cell (NK1.1 *CO3-) population and cytotoxicity against natural killer sensitive Yac-1 leukemic cell line. It was concluded that R. korthalsii methanol extract is a potential immunomodulator agent that could activate the natural killer cell. 0 2011 Academic Journals_ Author keywords